(untitled) (Damascus University Journal of agriculture sciences, 2021)
Research carried out at the Research and Studies Biological control Center - Faculty of Agriculture, University of Damascus during 2015-2016 season. Four species of entomopathogenic nematodes were used, they are: Steinernema feltiae Filipjev, S. carpocapsae (Weiser), Heterorhabditis bacteriophora Poinar and H. zealandica Poinar with three concentrations 500 - 1000 - 2000 / 1 ml of water was used to test its effectiveness within the laboratory conditions against larvae of the white grubs Anomala orientalis Waterh, wireworms Agriotes lineatus (Linnaeus), cutworms Agrotes ipsilon (Hufnagel). The results of the statistical analysis shoewd that H. zealandica was the effective species against Anomala oreintalis achieved 100% mortality, followed by H. bacteriophora where the percentage of death was (86.67%). H. zealandica was the effective species against A. lineatus comparing to other species and achieved 100% mortality, followed by H. bacteriophora (86.67%). H. zealandica, and S. feltiae where the effective species against A. ipsilon killing 100% of the cutworm larvae about four days. In the field the percentage of the control of Scarabaidae larvae was 40-55.6% when using H. bacteriophora, while this percentage rose using H. zealandica to 53.3-77.8%. The results of analysis of variance to showed that H. zealandica was better in controlling than H. bacteriophora using 1000-2000 dauer larvae / mL concentrations and was more efficient in the control